Dilematika “Keadaan Tertentu” Dalam Penjatuhan Sanksi Pidana Mati Terhadap Koruptor di Indonesia - Natasha Intania Sabila; Maharani Qaulan Syadidah Az Zahro; Balilah Rizki Putriga (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2023)
Phrase certain conditions are regulated by law as one of the reasons for imposing the death penalty on corruptors. Emergency management funds. As a serious crime, the threat of the death penalty for corruptors still leaves a variety of discourse between pro- and con-parties. This article aims to examine the consequences of death penalty sanctions in certain circumstances in terms of the effectiveness of imposing punishment on corruptors. This study uses normative legal methods. Data was callected from legal and statutory literature. The research results show that there are still multiple interpretations of the phrase "certain conditions" contained in Article 2 Paragraph 2 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. Corruption that has occurred as a national disaster means that the government has emphasized corruption as a serious act that causes the country to be unstable or in certain situations. Judges can define and provide parameters regarding "certain circumstances" so that death penalty sanctions can be executed. The repressive action of the death penalty can be an appropriate alternative sanction for extraordinary crimes and can be a law that does justice and balances the human rights of people who have been deprived of it.